A practical approach to investigating hospital-onset aspergillus - Eelco Meijer; Aleksandra Marek; Gordon Ramage; Anuradha Chowdhary; Linda Bagrade; Andreas Voss; Abhijit M Bal (Journal of Global Antimicrobial Resistance)
AIM: The aim is to develop an infection control action tool to aid investigation of hospital-onset Aspergillus. BACKGROUND: Aspergillosis has high mortality in immunosuppressed patients e.g. patients undergoing haematopoietic cell transplant. Infection control related actions to be undertaken in the event of single or multiple cases of hospital-onset Aspergillus have not been well described in literature. METHODS: We carried out an extensive literature review of infection control practices to develop an action tool for hospital-onset Aspergillus. RESULTS: Based on the duration between hospital admission and first isolation of Aspergillus, we categorise Aspergillus colonisation or infection into possible (2-14 days) and probable (>14 days) hospital-onset. For single cases not related to construction, we suggest a walk through inspection (checking for water related damage, presence of dust, fabric damage), maintenance records review, and retrospective case finding and prospective surveillance. Where cases are linked to construction, for infections caused by azole-resistant Aspergillus, and when investigating a cluster as part of a team exercise, we suggest a detailed inspection (review of HVAC system, filter inspection, cleaning of air ducts and ventilation grilles if required, checking insulation around ducts, and ascertaining air changes and pressure differential). Environmental sampling should be undertaken and antifungal prophylaxis reviewed if cases are linked to construction or where there are multiple cases. Molecular typing of environmental and clinical isolates should be considered. The degree of protective isolation needs to be taken into account. Table 1 describes our suggested approach. CONCLUSION: We propose a systematic approach to investigation of hospital-onset Aspergillus.